Efeitos da fotobiomodulação por diodos emissores de luz-led em células tumorais - Martins, Thaís Nogueira de Oliveira (2020)
Introdutction: Photobiomodulation is a widely used resource in the treatment of various clinical conditions and most diverse areas. However, its application in breast oncology is still quite limited for several reasons especially due to the lack of familiatity with the therapy and the uncertainty regarding the mechanisms of cellular, molecular and tissue action. Objective: To verify the effects of photobiomodulation by blue and red LED light-emitting diodes on the breast tumor lineage cells. Methods: In vitro experimental design in which breast cancer MCF7 strain tumor cells will be exposed to LED photobiomodulation with two distinct wavelengths (658 ηm and 470 ηm) and be accompanied by 1 (one), 2 (two) or 3 (three) days to verify the modulatory potential of irradiation. After the irradiation period, the cells were analyzed for parameters related to cell viability, proliferation, indirect production of nitric oxide (NO) and reactive oxygen species (ROS). Results: There was no increase in cell proliferation at any of the wavelengths. Three cumulative doses reduced cell viability. The blue light promotes a reduction in the production the NO and ROS. For red light, a single irradiation at 6J/cm² was able to promote an increase in NO rates and two cumulative doses at 19J/cm² increased the formation of ROS. Conclusion: Our findings showed that irradiation with blue and red light to 6J/cm² and 19J/cm² did not promote an increase in cell proliferation, on the contrary, three cumulative doses induced an increase in cell mortality.